A silvicultural management tool for the Oriental beech (Fagus orientalisLipsky) forests - Kara, Ferhat (Informa UK Limited, 2018)
ABSTRACTStand density management tools help forest managers and landowners to more effectively allocate growing space so that specific silvicultural objectives can be met. Due to the economic importance of Oriental beech (Fagus orientalis Lipsky) forests in Turkey, a stand density management tool was developed for this species to optimize regeneration success rate and tree growth. For the development of this tool, named stand density management diagram (SDMD), we utilized forest inventory data from the Kastamonu Regional Forest Directorate in Turkey. Previously published forest management approaches and models were employed during the development of the tool. The SDMD illustrates the relation among four forest indexes: the basal area per hectare, number of trees per hectare, forest stand volume per hectare, and quadratic mean diameter of the beech stands. The stand stocking percent (SSP) can be determined based upon any two of these four measurements. The results suggest that SSP is a better predictor of ...
Keywords: 15. Life on land